“Pearl Rush” and the Construction of Australian Imagination of Aru Islands, 1869-1937 - Rasyid, Rangga Ardia (Lembaran Sejarah, 2024)
In the early 20th century, the Aru Islands emerged as an economic centre in Eastern Indonesia’s lesser known region. Australian pearling industry entry into its maritime zone created the “Pearl Rush”. This western-mode of natural exploitation shaped Aru’s conception as a thriving pearling centre. This image of Aru was therefore a direct result of a constructed imagination reinforced by the active Australian pearling zone. Movement of Australian mariners and pearling fleets influenced the public views of the region, as reflected in the Australian newspapers and popular magazines. Such views connected the Aru Islands’ image into the greater “Pearl Zone” of North and Western Australian cities. This paper examines how Australia’s views of Aru’s natural resources impacted and shaped the understanding of the islands’ commercial role and it will highlight the role of the pearling industry in creating the allure of imagined valuable resources, which paved the way for its exploitation.